Trends in match injury risk in professional male rugby union: a 16-season review of 10 851 match injuries in the English Premiership (2002–2019): the Professional Rugby Injury Surveillance Project. Issue 12 (12th October 2020) - West, Stephen W; Starling, Lindsay; Kemp, Simon; Williams, Sean; Cross, Matthew; Taylor, Aileen; Brooks, John H M; Stokes, Keith A
Abstract : Objectives: The Professional Rugby Injury Surveillance Project is the largest and longest running rugby union injury surveillance project globally and focuses on the highest level of rugby in England. Methods: We examined match injuries in professional men's rugby over the period 2002/2003 to 2018/2019 and described trends in injuries over this time. Results: Over the period 2002/2003–2018/2019, 10 851 injuries occurred in 1 24 952 hours of match play, equating to a mean of 57 injuries per club per season and one injury per team per match. The mean incidence, severity (days absence) and burden (days absence/1000 hours) of injury were 87/1000 hours (95% CI 82 to 92), 25 days (95% CI 22 to 28) and 2178 days/1000 hours (95% CI 1872 to 2484), respectively. The tackle accounted for 43% injuries with running the second most common activity during injury (12%). The most common injury location was the head/face with an incidence of 11.3/1000 hours, while the location with the highest overall burden was the knee (11.1 days/1000 hours). Long-term trends demonstrated stable injury incidence and proportion of injured players, but an increase in the mean and median severity of injuries. Concussion incidence, severity and burden increased from the 2009/2010 season onwards and from 2011 to 2019 concussion was the most common injury. Conclusion: The rise in overall injury severity and concussion incidence are the most significant findings from this work and demonstrate the need for continued efforts to reduce concussion risk as well as a greater understanding of changes in injury severity over time.